Talent Management Influence on Organizational Learning Capabilities with Respect to the Mediating Role of Organizational Intelligence - mohammsd ghasemi; mahta joodzadeh; elham beigi rad (پژوهش‌های مدیریت عمومی, 2016)
In a rapidly changing environment, turbulent,unpredictable and full of uncertainty, organizations should have a productive,creative and continuous learning capability and potential in order to survive,grow, and accomplish goals in order to create superior value for all theirstakeholders, especially customers. Such a learning capability of organizationand its continuous development depends on numerous factors, includingorganizational intelligence and talent management. The research method is descriptive of Correlational. Thestatistical population consists In staff of Azad university of Zahedan (460), 210questionnaires were distributed ,of which 200were returned completedquestionnaires. So The sample size, 200.Simple random sampling method was usedin this study . Data collected by a questionnaire, That kind of contentvalidity Cronbach,s alpha which is related to reliability of the questionnaire obtained 0.937.Collected data analyzedin two different levels of descriptive and inferential statistics by SPSS 19software and  lisrel  were used . The research findings showed that;talent management has significant, positive and direct effect on organizationalintelligence, and learning capability while organizational intelligence has asignificant, positive and direct impact on organizational learning capability.The results also showed that organizational intelligence is mediation the relationshipbetween the talent management and organizational learning capability. Theresults of path analysis showed that the talent management has a significantand indirect impact on organizational capability through intelligence